2020
DOI: 10.1109/access.2019.2959633
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Bearingless Permanent-Magnet Motor for Axial Blood Pump Applications

Abstract: Because of their high power density and compact size, permanent-magnet (PM) motors have been commonly used to drive rotary blood pumps (RBPs), which are focused on the treatment of end-stage heart failure or as the bridge to a heart transplant. In this paper, a bearingless PM motor has been proposed for axial blood pump applications. The finite-element method (FEM) is used to predict the electromagnetic characteristics of the designed motor with improved performance. Two topologies are investigated, namely the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…From Figures 12,15,16, and 17, it can be concluded that the resultant radial force is about zero when the rotor is at the center, while the radial force is unsymmetrical. The resultant have high values when the rotor is displaced.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…From Figures 12,15,16, and 17, it can be concluded that the resultant radial force is about zero when the rotor is at the center, while the radial force is unsymmetrical. The resultant have high values when the rotor is displaced.…”
Section: Resultsmentioning
confidence: 95%
“…Figure 6 shows the 2-D FE model with a flux density plot. The motor is analyzed under underrated working conditions [15].…”
Section: Bldc Machine Modelmentioning
confidence: 99%
“…In the state -of-the-art VADs, there are two types of noncontact bearings: hydrodynamic bearings (Wang et al, 2020;Magari andHijikata, Journal of Advanced Mechanical Design, Systems, andManufacturing, Vol.16, No.3 (2022) Yamane et al, 2007) and active magnetic bearings (Greatrex et al, 2010;Habermann and Liard, 1980;Komori and Yamane, 2001;Osa et al, 2015;Weißbacher et al, 2010). In a hydrodynamic bearing system, the impeller is suspended by fluid forces generated in thin blood films between the impeller and pump housing (Fukushima et al, 2018;Aaronson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…M UCH attention is currently given to FSPMSMs to equip a variety of applications covering a wide range of power, from medical actuators and household appliances till wind turbines, going through electric and hybrid vehicles [1]- [5]. The great interest in FSPMSMs is motivated by [6]- [11]: (i) their low copper losses, (ii) their reduced cogging torque, (iii) their wide flux weakening range, and (iv) and their high fault tolerance capability thanks to their low mutual inductance.…”
Section: Introductionmentioning
confidence: 99%